Detection rate of FNA cytology in medullary thyroid carcinoma: a meta‐analysis. (14th August 2014) - Trimboli, Pierpaolo; Treglia, Giorgio; Guidobaldi, Leo; Romanelli, Francesco; Nigri, Giuseppe; Valabrega, Stefano; Sadeghi, Ramin; Crescenzi, Anna; Faquin, William C.; Bongiovanni, Massimo; Giovanella, Luca
Summary Background The early detection of medullary thyroid carcinoma (MTC) can improve patient prognosis, because histological stage and patient age at diagnosis are highly relevant prognostic factors. As a consequence, delay in the diagnosis and/or incomplete surgical treatment should correlate with a poorer prognosis for patients. Few papers have evaluated the specific capability of fine‐needle aspiration cytology (FNAC) to detect MTC, and small series have been reported. This study conducts a meta‐analysis of published data on the diagnostic performance of FNAC in MTC to provide more robust estimates. Research Design and Methods A comprehensive computer literature search of the PubMed/MEDLINE, Embase and Scopus databases was conducted by searching for the terms 'medullary thyroid' AND 'cytology', 'FNA', 'FNAB', 'FNAC', 'fine needle' or 'fine‐needle'. The search was updated until 21 March 2014, and no language restrictions were used. Results Fifteen relevant studies and 641 MTC lesions that had undergone FNAC were included. The detection rate (DR) of FNAC in patients with MTC (diagnosed as 'MTC' or 'suspicious for MTC') on a per lesion‐based analysis ranged from 12·5% to 88·2%, with a pooled estimate of 56·4% (95% CI: 52·6–60·1%). The included studies were statistically heterogeneous in their estimates of DR (I‐square >50%). Egger's regression intercept for DR pooling was 0·03 (95% CI: −3·1 to 3·2, P = 0·9). The study that reported the largest MTC series had a DR of 45%. Data on immunohistochemistry for calcitonin in diagnosing MTC were inconsistent for the meta‐analysis. Conclusions The presented meta‐analysis demonstrates that FNAC is able to detect approximately one‐half of MTC lesions. These findings suggest that other techniques may be needed in combination with FNAC to diagnose MTC and avoid false negative results.